Quantitative Measure of Self-Perceived Gender Relations in Young Women in the Mekong Delta of Vietnam - Thanh Cong Bui; Christine M Markham; Pamela M Diamond; Ly Thi-Hai Tran; Michael W Ross; Huong Thi-Hoai Nguyen; Thach Ngoc Le (Women’s Health Bulletin, 2017)
Background: The conceptualization and measurement of gender-based relations and equity are still challenging to researchers worldwide. Given a growing number of health studies which want to take into account the roles of gender relations, there is a need for quantitative measures of this determinant. Objectives: Based on the theory of gender and power and results from our previous qualitative work, this analysis aims to examine the applicability, reliability, and validity of a set of self-perceived gender-relation measures in the Mekong delta of Vietnam. Methods: Data came from a cross-sectional survey of 1181 undergraduate female students from two universities. Second-order latent variable modeling was used to examine applicability of theoretical structures and validity of measuring items. Single-factor modeling was employed to screen for the most relevant dimensions of self-perceived gender relations. Results: The second-order modeling showed good fit, suggesting that the theory well explained self-perceptions of gender relations. The consistency of models across 500 hypothetical bootstrapping samples further substantiated factorial validity of measures. Students who ever had a boyfriend held slightly different perceptions of gender relations compared to those who never had a boyfriend. Conclusions: The final parsimonious set of measures which had best loadings onto perceived subordination consisted of ten dimensions; this provides a practical application to measure self-perceived gender relations in other health research.